The effect of C–C motif chemokine ligand 2 supplementation on in vitro maturation of porcine cumulus-oocyte complexes and subsequent developmental competence after parthenogenetic activation - Kim, Sohee; Oh, Dongjin; Choi, Hyerin; Kim, Mirae; Cai, Lian; Jawad, Ali; Haomiao, Zheng; Lee, Joohyeong; Kim, Eunhye; Hyun, Sang-Hwan (Frontiers in Veterinary Science, 2023)
Porcine embryos are used for a variety of applications. However, the maturation rate in vitro remains low, and novel in vitro maturation (IVM) techniques that facilitate the collection of mature oocytes are necessary. C-C motif chemokine ligand 2 (CCL2) is a key periovulatory chemokine present in cumulus-oocyte complexes (COCs). We aimed to examine the effects of CCL2 supplementation during IVM on oocyte maturation and embryonic development. The CCL2 concentration was significantly higher in porcine follicular fluid (pFF) derived from follicles greater than 8 mm in size than in pFF derived from smaller follicles. There was a significant increase in CCL2 mRNA levels in all follicular cells after IVM compared with that before IVM. We analyzed the localization of CCL2 and its receptor, the CCL2 receptor, in follicular cells. During IVM, different concentrations of CCL2 were added to COCs cultured in a maturation medium. After IVM, the group treated with 100 ng/mL CCL2 showed significantly higher metaphase Ⅱ rates than the control group. All CCL2-treatment groups showed a significant increase in intracellular glutathione levels and a significant decrease in reactive oxygen species levels, compared to the control. In CCs treated with 100 ng/mL CCL2, the mRNA levels of BAX, CASP3, and NPR2 were significantly decreased. Furthermore, the mRNA levels of SOD1, SOD2, and CD44 were significantly increased. In oocytes treated with 10 ng/mL CCL2, mRNA levels of BAX and CASP3 were significantly decreased, whereas, NRF2 and NPM2 were significantly increased. ERK1 exhibited significantly increased mRNA expression in both CCs and oocytes treated with 10 ng/mL CCL2. The protein expression ratio of phosphorylated ERK1/2 to total ERK1/2 was significantly increased in CCs treated with 10 ng/mL CCL2. After parthenogenetic activation, cleavage rates were significantly improved in the 100 ng/mL CCL2 treatment group, and blastocyst formation rates were significantly enhanced in the 10 ng/mL CCL2 treatment group. Overall, our results suggest that IVM medium along with CCL2 improves porcine oocyte maturation and the development of parthenogenetically-activated embryos.